RESPONS SISWA TENTANG PENGGUNAAN MEDIA AUDIO VISUAL OLEH GURU PAI UNTUK MENINGKATKAN KONSENTRASI BELAJAR SISWA KELAS XI DI SMA NEGERI 03 TELUK KERAMAT - Yustina Yustina (Cross-border, 2022)
This study originated from looking at the phenomenon that occurs in a lack of student motivation in Islamic religious education subjects so that Islamic religious education teachers try to use media in learning. This study aims to obtain clear information about: 1) Describing student responses about the use of media by teachers in Islamic religious education for Class XI at SMA Negeri 03 Teluk Keramat, Teluk Keramat District, Academic Year 2019/2020. 2) Describe student learning outcomes after using audio visuals by PAI teachers to increase the concentration of class XI students in SMA Negeri 03 Teluk Keramat for the 2019/2020 academic year. The subjects of this study were teachers of Islamic religious education, and students of SMA Negeri 03 Teluk Keramat for the 2019/2020 academic year. To obtain data related to the research focus, the researcher conducted interviews, observation and documentation using interview guidelines, observation guidelines using a camera and a tape recorder as data collection tools. The data analysis technique used is qualitative data analysis. In this study, researchers used two techniques, namely: 1) Triangulation Technique, 2) Member Check Technique. The results of the study can be concluded: 1) Student responses regarding the use of media by teachers in learning Islamic religious education for Class XI at SMA Negeri 03 Teluk Keramat Sungai Baru District, Teluk Keramat District, Academic Year 2019/2020, namely: (a) Eager to listen to explanations of material using pictures containing explanations through audio-visual ablution and prayer. (b) Learning becomes fun, not bored because the material contains explanatory pictures through audio visuals about animal slaughter. (c) The pursuit becomes concentration in listening to the material because it contains explanatory pictures through audio-visuals about janazah prayers. 2) Student learning outcomes after using audio visuals by PAI teachers to increase the learning concentration of class XI students at SMA Negeri 03 Teluk Keramat Academic Year 2019/2020, namely: (a) The learning outcomes obtained are high reaching 80% after using audio visual media, the results can be known through evaluation. (b) The PAI teacher conducts a tutoring process for students who do not understand the material that has been delivered.